2004
DOI: 10.21273/hortsci.39.4.749c
|View full text |Cite
|
Sign up to set email alerts
|

Strip Tillage Pumpkin Production Using Rye, and Rye/Hairy Vetch Cover Crop

Abstract: Pumpkin is usually grown on bare ground. Weeds are controlled by pre-emergence herbicides and cultivation early in the season before pumpkin vines cover the ground. The pumpkin fruit lie on bare ground and covered with soil. In pick-your-own pumpkin operation it is impossible to walk on muddy fields to pick pumpkin fruits. Experiment was carried out using three treatments (Control-bare ground, Rye only mulch, and rye/hairy vetch mulch) replicated four times in complete randomized block design with plot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Similarly, Walters et al (2008) found that no-till pumpkin yields were nearly double conventional-till yields. On the other hand, Ogutu (2004) found that conventional-till resulted in greater pumpkin yields than striptill systems.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Similarly, Walters et al (2008) found that no-till pumpkin yields were nearly double conventional-till yields. On the other hand, Ogutu (2004) found that conventional-till resulted in greater pumpkin yields than striptill systems.…”
mentioning
confidence: 96%
“…Cover crop mulch can suppress weeds by physical interference and/or allelopathy throughout the production season (Barnes and Putnam, 1983;Creamer et al, 1996), which can potentially reduce the need for herbicides (Hartwig and Ammon, 2002). A thick cover crop residue layer can also keep fruits off the soil surface and relatively dry, which can help manage disease pressure and reduce the need for fungicides (Everts, 2002;Ogutu, 2004).…”
mentioning
confidence: 99%